Windows Vista in a Nutshell - Gralla, Preston (O'Reilly, 2011)
This unique reference thoroughly documents every important setting and feature in Microsoft's new operating system, with alphabetical listings for hundreds of commands, windows, menus, listboxes, buttons, scrollbars and other elements of Windows Vista. With this book's simple organization, you'll easily find any setting, tool, or feature for the task you want to accomplish.